Molecular epidemiology suggests Venezuela as the origin of the dengue outbreak in Madeira, Portugal in 2012–2013. (July 2015) - Franco, L.; Pagan, I.; Serre Del Cor, N.; Schunk, M.; Neumayr, A.; Molero, F.; Potente, A.; Hatz, C.; Wilder-Smith, A.; Sánchez-Seco, M.P.; Tenorio, A.
Abstract: An explosive epidemic occurred in Madeira Island (Portugal) from October 2012 to February 2013. Published data showed that dengue virus type 1 introduced from South America was the incriminated virus. We aim to determine the origin of the strain introduced to Madeira by travellers returning to Europe. Using phylogeographic analysis and complete envelope sequences we have demonstrated that the most probable origin of the strain is Venezuela.